Images of the community from Nietzsche’s thought - Buñuel Fanconi, Darío (Escritura e Imagen, 2023)
This article explores the idea of community in Nietzsche. This idea is not easily defined in his philosophy, which we consider to be an intentionally sought characteristic of his writing. What we propose, therefore, are images of the community from Nietzsche’s thought, possible interpretations of how the community could be thought from his philosophy. All these images have characteristics that go against the common conception of the community. It is not intended in this article to settle the issue but to enliven the reading and imagination of future interpreters of Nietzsche.The names we have given to our images are: the Landauerian community, the freak-show, the feast, the failed community, and the human-animal community.
Keywords: Nietzsche; Landauer; Community; Feast